Mohammad Ali Jazayery, E. Bagley Atwood: Observations on Loanwords as an Index to Cultural Borrowing Studies in Language, Literature and Culture of the Middle Ages and Later - Uribe-Villegas, Oscar (Revista Mexicana de Sociología, 2024)
-